In vivo efficacy of the histone deacetylase inhibitor suberoylanilide hydroxamic acid in combination with radiotherapy in a malignant rhabdoid tumor mouse model - Thiemann, Markus; Oertel, Susanne; Ehemann, Volker; Weichert, Wilko; Stenzinger, Albrecht; Bischof, Marc; Weber, Klaus-Josef; Lopez Perez, Ramon; Haberkorn, Uwe; Kulozik, Andreas; Debus, Jürgen; Huber, Peter E.; et al. (Radiation oncology, 2012)
Purpose: Histone deacetylase inhibitors are promising new substances in cancer therapy and have also been shown to sensitize different tumor cells to irradiation (XRT). We explored the effect as well as the radiosensitizing properties of suberoylanilide hydroxamic acid (SAHA) in vivo in a malignant rhabdoid tumor (MRT) mouse model. Methods and material: Potential radiosensitization by SAHA was assessed in MRT xenografts by analysis of tumor growth delay, necrosis (HE), apoptosis (TUNEL), proliferation (ki-67) and gamma H2AX expression as well as dynamic F-18-Fluorodeoxyglucose Positron Emission Tomography (F-18-FDG-PET) after treatment with either SAHA alone, single-dose (10 Gy) or fractionated XRT (3 x 3Gy) solely as well as in combination with SAHA compared to controls. Results: SAHA only had no significant effect on tumor growth. Combination of SAHA for 8 days with single-dose XRT resulted in a higher number of complete remissions, but failed to prove a significant growth delay compared to XRT only. In contrast fractionated XRT plus SAHA for 3 weeks did induce significant tumor growth delay in MRT-xenografts. The histological examination showed a significant effect of XRT in tumor necrosis, expression of Ki-67, gamma H2AX and apoptosis. SAHA only had no significant effect in the histological examination. Comparison of xenografts treated with XRT and XRT plus SAHA revealed a significantly increased gamma H2AX expression and apoptosis induction in the mice tumors after combination treatment with single-dose as well as fractionated XRT. The combination of SAHA with XRT showed a tendency to increased necrosis and decrease of proliferation compared to XRT only, which, however, was not significant. The 18F-FDG-PET results showed no significant differences in the standard uptake value or glucose transport kinetics after either treatment. Conclusion: SAHA did not have a significant effect alone, but proved to enhance the effect of XRT in our MRT in vivo model.